Unprecedented Thermo‐Enhanced Retainable Circularly Polarized Luminescence. Issue 1 (28th October 2022) - Qi, Weilin; Ma, Cheng; Liao, Peilong; Li, Hongpeng; Gu, Ting; Wu, Tongyue; Huang, Jianbin; Yan, Yun
Abstract: Circularly polarized luminescence (CPL) enabled by chiral self‐assembly is very promising in diversified applications. However, temperature‐triggered disassembly or self‐assembly transition often results in reduction or even silence of CPL. Here, a strategy of coordinating self‐assembly is reported that offers temperature enhanced and retainable CPL that is resistant to further temperature variation. Upon co‐assembling commercial dyes with the coordinating hydrogel of cholate‐calcium, the chirality transfer from cholate to the dyes allows generation of CPL. With increasing temperature, the CPL intensity can be enhanced 4 times and the emission dissymmetry factor g em can be promoted from 0.04 to 0.1, then they remain stable either upon further elevating or lowering temperature. Mechanism study reveals that increasing temperature has triggered the coordination transition between the carbonate groups and Ca 2+ from the metastable bidentate chelating to the thermal stable bridging mode, which drives the transition from flexible nanohelices to stiff helical bunches. This promotes the alignment of the dyes and in the meantime decreases its mobility, thus leads to increased CPL intensity and g em . It is envisioned that the strategy of coordinating self‐assembly would be very promising in creating thermally stable CPL for diversified applications. Abstract : Circularly polarized luminescence (CPL) enabled by chiral self‐assembly is very appealing in diversified applications. However, temperature‐triggered disassembly or self‐assembly transition often results in reduction or even silence of CPL. Here, thermo‐enhanced and retainable CPL with the highest g em of 0.1 is obtained with the aid of coordinating self‐assembly, which is very promising in the development of robust CPL materials.